External debts and economic growth in Malaysia - Siti Fazilah Alwi; Lee, Hock Ann; Nur Shahirah Azman; Lee, Huay-Huay (Human Resource Management Academic Research Society, 2020)
Previous researches on the relationship between external debt and economic growth in Malaysia have produced inconsistent results. Despite the intense debate on the link between external debt and economic growth, there is no research that takes the new definition of external debt into consideration. To address this issue, this study seeks to examine the effects of external debt on economic growth by allowing the external debt to be taken into consideration especially in terms of the non-residents holding of local-currency denominated debt securities. Using time series econometric approaches and quarterly data of Malaysia from 1997 Q1 to 2016 Q4, this study finds that there is a significant positive relationship between external debt and economic growth. In addition, the results of Granger causality test reveal the existence of short-run bilateral causality relationships between external debt and economic growth.